Hubungan Aktivitas Fisik dan Pola Makan Dengan Kejadian Dispepsia Pada Anak Remaja 16-18 Tahun - Halim, Yeni; Asykurni, Unzhurni; Hakim Nasution, Ikhwanul (Syntax Corporation, 2025)
Dyspepsia is a common upper gastrointestinal disorder among adolescents, characterized by symptoms such as epigastric pain, fullness, early satiety, or nausea. Lifestyle factors, including dietary patterns and physical activity, are thought to play a role in the occurrence of dyspepsia. This study aimed to analyze the relationship between physical activity and dietary patterns with the incidence of dyspepsia in adolescents. This was an analytical observational study with a cross-sectional design conducted at SMA Negeri 4 Medan in 2025. The study involved 92 students aged 16–18 years who met the inclusion criteria, selected using purposive sampling. Data were collected through a structured questionnaire covering physical activity, dietary patterns, and dyspepsia symptoms. Data analysis was performed using the Chi-Square test to determine the relationships between variables. The majority of respondents were 16 years old (63.0%) and male (67.39%). A total of 68.48% of respondents experienced dyspepsia. The Chi-Square test revealed a significant association between dietary patterns and dyspepsia incidence (p = 0.000), where respondents with poor dietary patterns had a higher incidence of dyspepsia compared to those with good dietary patterns. Conversely, physical activity showed no significant association with dyspepsia incidence (p = 0.297). There is a significant relationship between dietary patterns and dyspepsia among adolescents, while no significant association was found between physical activity and dyspepsia. Health education programs promoting healthy eating habits should be enhanced in school settings to prevent dyspepsia in adolescents.